2003
DOI: 10.1016/j.curtheres.2003.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of garcinia cambogia (Hydroxycitric Acid) on visceral fat accumulation: a double-blind, randomized, placebo-controlled trial

Abstract: G cambogia reduced abdominal fat accumulation in subjects, regardless of sex, who had the visceral fat accumulation type of obesity. No rebound effect was observed. It is therefore expected that G cambogia may be useful for the prevention and reduction of accumulation of visceral fat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 32 publications
(23 reference statements)
3
62
0
2
Order By: Relevance
“…However, numerous clinical studies have also provided evidences that G. cambogia extract (HCA) does not ameliorate obesity (30)(31)(32)(33)(34). In addition, potential testicular toxicity of G. cambogia extract at high doses was reported in an obese animal model (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, numerous clinical studies have also provided evidences that G. cambogia extract (HCA) does not ameliorate obesity (30)(31)(32)(33)(34). In addition, potential testicular toxicity of G. cambogia extract at high doses was reported in an obese animal model (35).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently in vitro and in-vivo studies revealed that HCA not only inhibited the action of citrate lyase and suppressed de novo fatty acid synthesis (Lowenstein, 1971) but also increased rates of hepatic glycogen synthesis (Sullivan, Triscari, & Neal Miller, 1974), suppressed food intake (Sullivan, Triscari, Hamilton, & Neal Miller, 1973) and decreased body weight gain (Nageswara Rao & Sakeriak, 1988). Recently it has been established that a high dose of HCA was effective in suppressing fat accumulation in developing male Zucker obese rats but was found to be highly toxic to the testis (Hayamizu et al, 2003;Saito et al, 2005). Various salts of this naturally occurring HCA are now being used in nutraceuticals and incorporated into many preparations in weight management and are sold over-the-counter to consumers all over the world (Hobbs, 1994).…”
Section: Introductionmentioning
confidence: 96%
“…Також під дією ГЛК відбувається активація ферменту карнітинацилтрансферази, завдяки чому активується утворення карнітину й, відповідно, по-силюється транспорт внутрішньоклітинних жирних кислот у мітохондрії та їх окислення [9]. Результатом блокади АТФ-цитратліази та активації карнітин-ацилтрансферази є зниження ліпогенезу.…”
unclassified